2013
DOI: 10.1371/journal.pone.0058411
|View full text |Cite
|
Sign up to set email alerts
|

Chemotaxonomic Study of Citrus, Poncirus and Fortunella Genotypes Based on Peel Oil Volatile Compounds - Deciphering the Genetic Origin of Mangshanyegan (Citrus nobilis Lauriro)

Abstract: Volatile profiles yielded from gas chromatography-mass spectrometry (GC-MS) analysis provide abundant information not only for metabolism-related research, but also for chemotaxonomy. To study the chemotaxonomy of Mangshanyegan, its volatile profiles of fruit and leaf and those of 29 other genotypes of Citrus, Poncirus, and Fortunella were subjected to phylogenetic analyses. Results showed that 145 identified (including 64 tentatively identified) and 15 unidentified volatile compounds were detected from their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 39 publications
4
35
0
Order By: Relevance
“…Quantitaive analysis of various compound groups indicated that monoterpenes and sesquiterpenes were dominant. This result was similar to the composition of essential oils from Citrus nobilis, in which monoterpenes and sesquiterpenes were dominant (Liu et al, 2013). Similar report was found on the essential oils of Citrus limetta, with sesquiterpenes being the most abundant compared to other compounds (Colecio-Juárez et al, 2012).…”
Section: Discussionsupporting
confidence: 87%
“…Quantitaive analysis of various compound groups indicated that monoterpenes and sesquiterpenes were dominant. This result was similar to the composition of essential oils from Citrus nobilis, in which monoterpenes and sesquiterpenes were dominant (Liu et al, 2013). Similar report was found on the essential oils of Citrus limetta, with sesquiterpenes being the most abundant compared to other compounds (Colecio-Juárez et al, 2012).…”
Section: Discussionsupporting
confidence: 87%
“…Cluster analysis was used to classify the volatile chemicals through the cosine correlation analysis method on the basis of the concentrations of the volatile chemicals, which was conducted by the software IBM‐SPSS 19.0. The same statistical software was used for the significance test and principal component analysis (PCA) of odour characteristics according to previous methods . One‐way analysis was performed by anova and Duncan's multiple range test to show the significant statistical differences…”
Section: Methodsmentioning
confidence: 99%
“…Over 300 aroma volatiles have been reported for fresh orange juice . Several studies have been performed on aroma volatiles in mandarin peel oil and essence, as well as in fresh fruits, although most of them have studied only one or a few genotypes. Tietel et al .…”
Section: Introductionmentioning
confidence: 99%
“…Over 300 aroma volatiles have been reported for fresh orange juice. 5 Several studies have been performed on aroma volatiles in mandarin peel oil and essence, [6][7][8][9][10][11][12] as well as in fresh fruits, [13][14][15][16][17][18] although most of them have studied only one or a few genotypes. Tietel et al 4 summarized 37 consensus aroma volatiles in mandarin juice and nine of them were considered to be mandarin core aroma volatiles.…”
Section: Introductionmentioning
confidence: 99%